2010
DOI: 10.2353/ajpath.2010.090825
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Toxoplasma gondii Cysts from the Brain by Perforin-Mediated Activity of CD8+ T Cells

Abstract: Chronic infection with؉ T cells does not require their production of interferon-␥, the major mediator to prevent proliferation of tachyzoites during acute infection, but does require perforin. These results suggest that CD8 ؉ T cells induce elimination of T. gondii cysts through their perforin-mediated cytotoxic activity. Our findings provide a new mechanism of the immune system to fight against chronic infection with T. gondii and suggest a possibility of developing a novel vaccine to eliminate cysts from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
178
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(183 citation statements)
references
References 41 publications
(24 reference statements)
3
178
1
1
Order By: Relevance
“…Although adoptive transfer of perforin-deficient CD8 ϩ T cells is effective at preventing TE, recent work supports the model of cytolytic cyst control, as transferred IFN-␥-deficient CD8 ϩ T cells are able to greatly reduce cyst burden in a chronic reactivation model (44). The multifaceted effects of IFN-␥ on the immune system make it difficult to separate the contribution of CD8 ϩ T cell IFN-␥ from that of other sources of this cytokine.…”
Section: Ifn-␥-producing Cells: From T To Nk Cells and Neutrophilsmentioning
confidence: 95%
“…Although adoptive transfer of perforin-deficient CD8 ϩ T cells is effective at preventing TE, recent work supports the model of cytolytic cyst control, as transferred IFN-␥-deficient CD8 ϩ T cells are able to greatly reduce cyst burden in a chronic reactivation model (44). The multifaceted effects of IFN-␥ on the immune system make it difficult to separate the contribution of CD8 ϩ T cell IFN-␥ from that of other sources of this cytokine.…”
Section: Ifn-␥-producing Cells: From T To Nk Cells and Neutrophilsmentioning
confidence: 95%
“…The latent stage is associated with marginal inflammation and cell recruitment to the CNS, which is necessary to provide adequate IFN-g levels, the major driving force for parasite control. In the murine models of chronic infection, the characteristics of T cell subsets (24,(63)(64)(65), specific mononuclear cells, for example, resident microglia and APCs, have been extensively studied. In contrast, the role of the newly described myeloid cell subsets is controversial and thus requires further investigation (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited access, the CNS is inundated by immune cells from the periphery during the chronic stage of T. gondii infection. The adaptive immune responses in the CNS have been extensively investigated, describing an important contribution to the local parasite control (22)(23)(24)(25). Besides, several studies have highlighted the function and phenotype of certain mononuclear cells such as microglia, brain DCs, and macrophages upon cerebral toxoplasmosis; however, the role of recruited newly described myeloid cell subpopulations remains undefined (19,26,27).…”
mentioning
confidence: 99%
“…As mentioned earlier, previous studies in chronic T. gondii model have demonstrated that cytotoxicity and, especially, IFN-␥ production are critical effector mechanisms for CD8 ϩ T cell-mediated parasite control (15,37,44). The differential contributions of these effector mechanisms to short-term parasite control by donor CD8 ϩ T cells need to be assessed.…”
Section: Cd8mentioning
confidence: 99%